Development of add-ins macros in Microsoft PowerPoint for enhancing animation of logic circuits - Goh, Wei Chen. (2013)
Microsoft Office PowerPoint has been widely used in the area of presentation. The aim of this project is to go in depth into the already incorporated Visual Basic within the Microsoft Office PowerPoint to fully utilize it for an engineering student who may need to draw logic gates for their presentation or school projects. The development of this feature into PowerPoint has its limitation as the Visual Basic software has its limits as compared to other types of computer language widely used today. We will go in depth into understanding the digital circuits (logic gates), comparison of currently available digital logic circuit designer software in the market today and also the process of developing our own simple logic gate designer software to be incorporated into Microsoft PowerPoint. With this add-in macros created we hope it will ease the difficulty for anyone who has the need to draw or present a logic gate or a complex circuit on PowerPoint.